Práticas de gestão com contribuição para a responsabilidade social corporativa: estudo de caso em uma empresa de energia - Ramalho, Luciano da Silva (2006)
This paper is mainly intended to study the management practices that can direct or indirectly contribute to the social responsibility management of a company before its stakeholders and subsequently list them according to the proposed different levels of social responsibility. In this respect, it presents and discusses as methodological option a case study worked out in an energy company of great magnitude, more specifically in the organizational unit in charge of project implementation. In that light, this paper identifies the major management practices developed either on the corporation or the studied unit levels. Once such practices are identified, they are listed at three proposed social responsibility levels: Social Obligation, Social Responsibility and Social Sensitivity. Taking into consideration the results found, it was possible to conclude that the management practices placed on low and high levels (respectively social obligation and social sensitivity) represent a corporation attitude, while the practices placed on the intermediate level (social responsibility) represent in general a singular attitude, which customarily occurs at organizational unit level.